Cognitive Behaviour Therapy (CBT) Lowers Online Game Addiction Rates in Adolescents - Hotma Roiningsih Tambunan; Kumboyono Kumboyono; Retno Lestari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
High curiosity in adolescents is often shown by playing online games excessively. Continuous and excessive use of online games has many negative impacts, including reduced sleep duration, reduced focus on learning, and increased financial costs incurred. Action that can be given to overcome the negative impact of using online games is the provision of psychotherapy. Psychotherapy that can be given and is believed to be able to reduce the level of online game addiction in adolescents is cognitive behavior therapy (CBT). This study aims to identify the benefits of CBT in reducing online game addiction in adolescents. This type of research is quasi-experimental with a nonequivalent control group design. The research subjects were divided into two groups: the intervention group (23 people) and the control group (23 people). The research was conducted at the Malang National Vocational School in September-November 2022. Data were analyzed using the Wilcoxon and Mann-Whitney tests. This study showed that the treatment group's average value of online game addiction statistically decreased with a p-value of 0.000 (p less than 0.05). In contrast, in the control group, there was no difference in the p-value of 0.059. A different test for the two groups yielded a p-value of 0.000. From these results, it can be seen that there is a difference in the level of online game addiction between the treatment and control groups. Giving CBT to adolescents is statistically proven to reduce addiction to online games so that adolescents can improve their quality of life by carrying out positive activities that benefit them. Abstrak: Rasa keingintahuan yang tinggi pada remaja sering ditunjukkan dengan bermain game online secara berlebihan. Penggunaan game online yang dilakukan secara terus menerus dan berlebihan memiliki banyak dampak negatif, antara lain berkurangnya durasi tidur, fokus belajar berkurang, dan meningkatnya biaya finansial yang dikeluarkan. Tindakan yang dapat diberikan dalam mengatasi dampak negatif penggunaan game online yaitu pemberian psikoterapi. Psikoterapi yang dapat diberikan dan dipercaya dapat menurunkan tingkat adiksi game online pada remaja yaitu cognitive behavior therapy (CBT). Studi ini bertujuan mengidentifikasikan manfaat pemberian CBT dalam menurunkan tingkat adiksi game online pada remaja. Jenis penelitian ini adalah quasi-experimental dengan rancangan nonequivalent control group design. Subjek penelitian dibagi menjadi dua kelompok yaitu kelompok intervensi (23 orang) dan kelompok kontrol (23 orang). Penelitian dilakukan di SMK Nasional Malang pada bulan September-November tahun 2022. Data dianalisis menggunakan uji Wilcoxon dan Mann-Whitney. Hasil penelitian ini menunjukan nilai rata-rata tingkat adiksi game online pada kelompok perlakuan secara statistik mengalami penurunan dengan p-value 0,000 (p kurang dari 0,05), sedangkan pada kelompok kontrol tidak terdapat perbedaan p-value 0.059. Uji beda dua kelompok didapatkan hasil p-value 0.000, dari hasil ini terlihat ada perbedaan tingkat adiksi game online antara kelompok perlakuan dan kontrol. Pemberian CBT pada remaja secara statistik terbukti menurunkan tingkat adiksi game online, sehingga remaja dapat meningkatkan kualitas hidup dengan melakukan aktivitas positif yang bermanfaat bagi remaja.